Didactic Suitability Assessment Guide of Educational Processes for the Differential - Verón, Manuel Alejandro (2024)
[Objective] This article describes the process of preparing a Guide for the Assessment of Didactic Suitability of a process for studying the concept of the differential of a function. The objective of this exercise was to propose an instrument to promote, guide and support teachers’ analysis of, and reflection on, teaching and learning processes of the differential concept. [Methodology] The research method used was content analysis, and its starting point was a systematic review of didactic-mathematical knowledge in key research. The analysis was guided by the dimensions or facets that characterize an educational process – epistemic, cognitive, affective, instructional and ecological – whose components and criteria are based on the notion of didactic suitability proposed in the Onto-semiotic Approach to Mathematical Knowledge and Instruction (OSA). [Results] The construction of the Didactic Suitability Assessment Guide introduced a methodology for the reconstruction of the reference meaning for the study of various facets of the differential. In addition, this guide represents a powerful tool for teachers at the time of designing, implementing. and evaluating study processes, taking into account the various meanings of the differential, its connections, its potential semiotic conflicts and its relationships with other concepts. [Conclusions] In line with the theoretical reference framework, it is concluded that its ideal use would allow teachers to make informed decisions about management of the didactic process, taking into account its educational context.